Integrasi Program Madrasah Diniyah sebagai Model Penguatan Pendidikan Karakter Religius di SMPN 6 Sudimoro: Integration of the Madrasah Diniyah Program as a Model for Strengthening Religious Character Education at SMPN 6 Sudimoro - Rahmawatunnisa Awaliyah; M. Fahmi Maulana; Siti Khurota A’yunin (ITScience (Information Technology and Science), 2026)
This study aims to examine the integration of the Madrasah Diniyah program at SMPN 6 Sudimoro as a strategy for strengthening students' religious character. The study focuses on the integration model, implementation patterns, implications for character formation, and supporting and inhibiting factors in program implementation. This study uses a descriptive qualitative approach with a case study design. Data collection was conducted through in-depth interviews with the principal, teachers, and parents, participant observation of religious activities, and analysis of curriculum documents and school reports. Data analysis techniques refer to the interactive model of Miles and Huberman, which involves data reduction, presentation, and conclusion. The results show that the integration of the Madrasah Diniyah program at the school is an independent initiative designated as a mandatory activity. Based on Thomas Lickona's character education theoretical framework, this program successfully touches three main dimensions: strengthening moral knowledge through materials on adab, basic fiqh, and reading and writing the Qur'an; fostering moral feelings through internalizing religious values in the school environment; and realizing moral actions through the habituation of worship and noble morals in daily life. Key supporting factors include strong synergy among the school, parents, and teaching staff, as well as support from local government policies. Conversely, limited learning time and diverse student backgrounds pose strategic challenges. These findings emphasize that multi-stakeholder collaboration is key to internalizing religious values without disrupting the national curriculum, and they also recommend regular evaluation to ensure program sustainability.